The Socio-Cultural Impacts of Rural Tourism Development: A Case Study of Tanjung Tourist Village in Sleman Regency - Nurlena Nurlena; Riza Taufiq; Musadad Musadad (Jurnal Kawistara, 2021)
It has been commonly understood that tourism development in rural areas can generate a unique dynamic in the social life of the village communities. This includes a recognition of the collective and cohesive village communities. The significance of socio-cultural factors in tourism is reflected in many villages in Yogyakarta. Taking a case study in Tanjung village as a rural tourism destination in Sleman Regency, Yogyakarta, this study investigated the social and cultural impacts of rural tourism development on the host community. By using a qualitative method, the data in this study came from in-depth interviews with the head of village tourism management and village residents, focus group discussions, and field observations. As the result, this study found that rural tourism has brought a positive impact on community involvement and empowerment, including women. In addition, the host-visitor interactions are positive but superficial. From the cultural aspect, tourism has played an important role in the preservation of local culture and arts. Several local art performances and traditions have been revived due to tourism. However, apart from the positive impacts, the development of rural tourism has generated problems that could turn into conflicts among community members, especially those concerning dualistic tourism management and negative perception over economic benefit distribution.